The Degree of the Employment of the First Three Grade Teachers of Distance learning applications in teaching in light of Corona Pandemic in Northwest Badia District from their point of view - Abu Kaf, Shoma Suleiman Muhammad (Journal of Educational and Psychological Sciences, 2022)
This study aimed at identify at the degree of the employment of the first three Grade teachers of the distance learning applications in teaching in light of the corona pandemic in Northwest Badia District from their point of view, The study followed the descriptive method, To collect data, a questionnaire was developed, consisting of (26) items, The validity and reliability of the instrument have been verified through applying on a sample of (79) teachers chosen by using stratified random sample method. The results of the study showed that the degree of the employment of the first three Grade teachers of the distance learning applications in teaching in light of the corona pandemic in Northwest Badia District from their point of view as a whole is medium, The field of employing social networking sites ranked first, with a high degree, followed by the field of employing your darsak platform, at a medium degree, followed by the field of employing virtual classes, with a medium degree, and in the last place, the field of employing the interactive Microsoft Teams platform, and at a medium degree. The results indicated that there were no statistically significant differences at level (α ≤ 0.05) between the average responses of the estimates of the individuals of the study sample in the degree of the employment of the first three Grade teachers of the distance learning applications to variables of sex, or experience. In light of the results, the study recommends a set of recommendations, the most important of which are holding training courses for teachers on distance learning applications.